PAHs in fly ash from lignite combustion - Stefanova, M.; Marinov, S. P.; Gonsalvesh, L.; Mastral, A.; Callen, M.; Gadjanov, P. (Bulletin of the Geological Society of Greece, 2007)
This paper describes state-of the art for isolation and determination of polycyclic aromatic hydrocarbons (PAHs) in fly ash from lignite combustion in Maritza East Thermal Power Plant, Bulgaria. Total sum of-17 microg/kg solid by-product PAHs was determined. The profile of PAHs distribution according to the number of aromatic rings in the molecule (R) was determined. Organic extracts were mainly composed by PAHs, their alkylated homologues and heteroatom containing counterparts with dominance of three/four cyclic aromatic compounds. Respectively, relative carcinogenic potency values for PAHs compared to Benzofajpyrene with TEFEPA =1 was not high - 0,07385. Seventeen PAHs, some of them in the list of USEPA for priority pollutants with expressed carcinogenic/mutagenic potential, were identified and quantified by mass spectroscopy (GC/MS/MS) and d-PAHs as internal standards. Determined values for contents of PAHs under regulation were lower than their backgrounds in Bulgarian soils. Nevertheless PAHs in combustion fly ash should be monitored because of high solid by-products annual production and problems of reuse